2000
DOI: 10.1073/pnas.100128297
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide-3 kinase binds to a proline-rich motif in the Na + ,K + -ATPase α subunit and regulates its trafficking

Abstract: Endocytosis of Na + ,K + -ATPase molecules in response to G protein-coupled receptor stimulation requires activation of class I A phosphoinositide-3 kinase (PI3K-I A ) in a protein kinase C-dependent manner. In this paper, we report that PI3K-I A , through its p85α subunit-SH3 domain, binds to a proline-rich region in the Na + ,K + -ATPase catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
126
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 52 publications
(58 reference statements)
1
126
0
Order By: Relevance
“…Binding of TCTP to the a1 subunit of Na,K-ATPase induces the release and activation of Src Recent studies suggest that phosphatidylinositol 3-kinase (PI3K) binds to the N-terminal proline-rich motif of Na,K-ATPase a subunit and that partial inhibition of Na,K-ATPase by ouabain induces Src binding to the Na,K-ATPase a subunit (Yudowski et al, 2000;Tian et al, 2006). We found that TCTP bound to the Na, K-ATPase a subunit partially inhibits its pumping activity (Jung et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Binding of TCTP to the a1 subunit of Na,K-ATPase induces the release and activation of Src Recent studies suggest that phosphatidylinositol 3-kinase (PI3K) binds to the N-terminal proline-rich motif of Na,K-ATPase a subunit and that partial inhibition of Na,K-ATPase by ouabain induces Src binding to the Na,K-ATPase a subunit (Yudowski et al, 2000;Tian et al, 2006). We found that TCTP bound to the Na, K-ATPase a subunit partially inhibits its pumping activity (Jung et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the p85 subunit of PI3 kinase can also directly interact with the Na + /K + ATPase (Chibalin et al 1998;Yudowski et al 2000). Adaptin binds to cargo proteins, recruits clathrin and promotes the formation of clathrin-coated pits (Kirchhausen 2000), triggering an endocytotic process of the Na + /K + ATPase that reduces sodium pump activity in the kidney and causes a decreased Na + reabsorption upon dopamine stimulation.…”
Section: Polymorphisms In Adducin Genesmentioning
confidence: 99%
“…However, phosphorylation may not affect the intrinsic properties of the Na ϩ ,K ϩ -ATPase (i.e., catalytic activity) but their subcellular distribution. For example, in renal epithelial cells inhibition of Na ϩ ,K ϩ -ATPase activity by catecholamines or phorbol esters is mediated by phosphorylation of the catalytic ␣-subunit, and this event does not affect the catalytic properties of the enzyme while in the plasma membrane but constitutes the triggering signal for its endocytosis into endosomes via a clathrin vesicle-dependent mechanism (Chibalin et al, 1997Yudowski et al, 2000;Efendiev et al, 2002). By contrast, in lung alveolar epithelial cells isoproterenol or DA increase Na ϩ , K ϩ -ATPase activity and this effect is associated with an increased recruitment of active Na ϩ , K ϩ -ATPase molecules to the plasma membrane Lecuona et al, 2000;Ridge et al, 2002).…”
Section: Introductionmentioning
confidence: 99%